SIMO DC/DC converter - Wong, Jia Jie (Nanyang Technological University, 2023)
In multi-input and multi-output applications, multiport converters outperform conventional solutions that use multiple single converters. Furthermore, they provide the most cost-effective operation and improve system performance. As a result, much development and research has been done in recent years to develop single-input-multi-output (SIMO) converters in various aspects. In this project, the goal is to design a functional SIMO DC-DC converter based on a single output converter and then based on the simulations of the designed SIMO DC-DC converter to obtain the best possible performance. The first step in the project is to grasp the idea of a DC-DC converter. The next step is to comprehend how the provided single inductor single output converter design works. Next, I'll convert it to a SIMO DC-DC converter. There are three methods that were applied to obtain multiple outputs without regard for performance. The first method focuses exclusively on obtaining multiple outputs regardless of the size or number of transistors used. The second version uses a decoder and a transmission gate to turn on and off a single output path in a cycle. This technique does not keep the output voltage of one output constant while providing current to other outputs. As a result, the third implementation will solve this issue. The third technique will delve deeper into the control logic circuit to obtain multiple outputs. A portion of the project was completed by obtaining numerous outputs from the given circuit using only one inductor. However, the third method has some flaws, and optimal performance was not obtained due to time constraints.